Sterilisation of Dental Implant Surgical Instruments, Office Area and Implant Components: A Narrative Review - Deepesh Kumar Gupta; K Seethal; Jenifer Keretta; Mahendra Kumar Anant; Sravani Vattigunta (Journal of Clinical and Diagnostic Research)
Implant surgical procedures require meticulous attention to sterilisation protocols to prevent infections and ensure successful outcomes. Various sterilisation methods, such as steam sterilisation, ethylene oxide sterilisation and hydrogen peroxide plasma sterilisation, are commonly used in healthcare facilities. Each method has its advantages and limitations and the selection of a sterilisation method depends on factors such as the type of implant material, instrument design and compatibility with the sterilisation process. Proper handling, packaging and storage of implant surgical components and instruments are essential to maintain their sterility until they are used. Healthcare facilities must follow standardised protocols and guidelines to ensure the effective sterilisation of implant surgical components and instruments, ultimately reducing the risk of infections and improving patient outcomes. Controversies exist regarding the reusability of healing abutments, with some advocating for single-use only to reduce the risk of contamination, while others argue for reusability under stringent sterilisation protocols. Further research is needed to establish clear guidelines on the reuse of healing abutments in implant surgery. The sterilisation of implant surgical components and instruments is a critical aspect of implant surgery that requires careful consideration of sterilisation methods and adherence to established protocols. Addressing the controversies surrounding the reusability of certain components, such as healing abutments, is essential to ensure patient safety and improve surgical outcomes.